2005
DOI: 10.1002/path.1805
|View full text |Cite
|
Sign up to set email alerts
|

Plasmalemmal vesicle-associated protein (PLVAP) is expressed by tumour endothelium and is upregulated by vascular endothelial growth factor-A (VEGF)

Abstract: Vascular endothelial growth factor-A (VEGF) is an important regulator of vascular permeability. In preclinical studies, VEGF induces endothelial fenestrations in pre-existing and neo-vasculature, while inhibition of VEGF leads to a reduction in endothelial fenestrations. Recently, vascular regression in response to VEGF inhibition has been shown to correlate with the presence of endothelial fenestrations. Plasmalemmal vesicle-associated protein (PLVAP) is believed to be a component of diaphragmed endothelial f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
105
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(119 citation statements)
references
References 55 publications
(114 reference statements)
6
105
1
Order By: Relevance
“…36 Vascular endothelial growth factor (VEGF), which is secreted from podocytes in mature glomeruli, plays a crucial role in the formation and maintenance of fenestrae in GEnC, as well as in various endothelial cell types. [37][38][39][40] VEGF has also been reported to upregulate the expression of PV-1 mRNA and protein in human endothelial cell 41,42 ; however, most GEnC in mature glomeruli do not express PV-1, as reconfirmed in this study. This inconsistence presumably indicates that the intracellular signaling pathways for the formation of fenestrae and the upregulation of PV-1 are not completely identical.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…36 Vascular endothelial growth factor (VEGF), which is secreted from podocytes in mature glomeruli, plays a crucial role in the formation and maintenance of fenestrae in GEnC, as well as in various endothelial cell types. [37][38][39][40] VEGF has also been reported to upregulate the expression of PV-1 mRNA and protein in human endothelial cell 41,42 ; however, most GEnC in mature glomeruli do not express PV-1, as reconfirmed in this study. This inconsistence presumably indicates that the intracellular signaling pathways for the formation of fenestrae and the upregulation of PV-1 are not completely identical.…”
Section: Discussionsupporting
confidence: 77%
“…Upregulation of PV-1 requires the activation of phosphatidylinositol 3-kinase and p38 mitogen-activated protein kinase. 41,42 VEGF-phosphatidylinositol 3-kinase-p38 mitogen-activated protein kinase pathway is a candidate for the mechanisms involved in the upregulation of PV-1 in the GEnC of immature and Thy-1.1 nephritic glomeruli. In most GEnC without diaphragms, however, this pathway may be inactivated in adult mature glomeruli by some yet unknown mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Strickland et al (40) reported that PV-1 expression induced by VEGF is p38 MAP kinase dependent (40), whereas there was no data about the effect of ANG II on PV-1 expression. Here, we demonstrated that ANG II induced PV-1 expression, similarly to VEGF, also in a p38-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were then treated with various doses of ANG II or 100 ng/ml VEGF for 24 and 48 h. RNAs were isolated using GenElute Mammalian Total RNA Kit (Sigma) and later transcribed to cDNAs with TaqMan Reverse Transcription kit (Applied Biosystems) on a Bio-Rad iCycler thermal cycler. PV-1 real-time PCR was performed using a TaqMan assay published previously (40) in a Bio-Rad CFX96 thermal cycler. Data were normalized to ribosomal RNA content (TaqMan Ribosomal RNA control reagents, Applied Biosystems, Forster City, CA), relative quantitation being performed using the Bio-Rad CFX Manager Software v. 1.7.…”
Section: Assessment Of Pv-1 Mrna Expression By Real-time Pcrmentioning
confidence: 99%
See 1 more Smart Citation